Damping behavior of hygrothermally conditioned carbon fiber/epoxy laminates - Botelho, E. C. [UNESP]; Pardini, L. C.; Rezende, M. C. (Wiley, 2007)
Carbon fiber reinforced polymer composites have been used in wide variety of applications including, aerospace, marine, sporting equipment as well as in the defense sector due to their outstanding properties at low density. In many of their applications, moisture absorption takes place which may result in a reduction in mechanical properties even at lower temperature service. In this work, the viscoelastic properties, such as storage modulus (E′) and loss modulus (E″), were obtained through vibration damping tests for three carbon fiber/epoxy composite families up to the saturation point (6 weeks). Three carbon fiber/epoxy composites having [0/0] s, [0/90] s, and [±45] s orientations were studied. During vibration tests the storage modulus (E′) and loss modulus (E″) were monitored as a function of moisture uptake, and it was observed that the natural frequencies and E′ values decreased with the increase during hygrothermal conditioning due to the matrix plasticization. © 2007 Wiley Periodicals, Inc.
Keywords: Carbon fiber/epoxy; Damping behavior; Hygrothermal conditioning; Viscoelastic properties; Carbon fiber reinforced plastics; Damping; Epoxy resins; Laminates; Thermal effects; Viscoelasticity; Carbon fibers; carbon fiber; composite property; epoxy resin; fiber reinforced composite; laminate; moisture; viscoelasticity